2007
DOI: 10.1160/th07-03-0209
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-converting enzyme insertion/deletion polymorphism and serum levels of angiotensin-converting enzyme in venous thromboembolism

Abstract: The angiotensin-converting enzyme (ACE) has been suggested to affect blood coagulation and fibrinolysis. Results from literature on the role of the frequent insertion/deletion (I/D) polymorphism in the ACE gene in venous thromboembolism (VTE) are controversial. Only limited data on ACE serum levels inVTE exist. We determined the ACE I/D polymorphism by genotyping and ACE serum levels by an enzymatic assay in 100 high-risk patients with objectively confirmed recurrentVTE and at least one event of an unprovoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
(23 reference statements)
2
21
1
1
Order By: Relevance
“…Namely, the ACE DD genotype is associated with higher levels of serum ACE (Ay et al 2007). A number of studies have confirmed that individuals with the DD genotype have a higher incidence of myocardial infarction and other cardiovascular disorders, and even sudden cardiac death (Gard 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the ACE DD genotype is associated with higher levels of serum ACE (Ay et al 2007). A number of studies have confirmed that individuals with the DD genotype have a higher incidence of myocardial infarction and other cardiovascular disorders, and even sudden cardiac death (Gard 2010).…”
Section: Discussionmentioning
confidence: 99%
“…ACE gene, which contains 26 exons and 25 introns, is located on chromosome 17q23 (Tiret et al 1992). Although there are many identified polymorphic sites in ACE gene, some of which located in the coding regions of this gene, polymorphism rs4646994 defined by the presence (insertion, I allele), or the absence (deletion, D allele) of 287-base pair (bp) Alu fragment in intron 16 of the gene, is by far the best studied (Folland et al 2000;Ay et al 2007). This polymorphism, unlikely functional due to its location, can explain nearly a half of the inter-individual variation in production and activity of ACE, both in tissues and in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that allele I of ACE gene is associated with lower ACE levels, whereas D allele is associated with increased ACE activity (10). According to the meta-analysis results performed by Zhang, the D allele of ACE I/D polymorphism is a low-penetrance susceptibility marker of ischemic stroke (9).…”
Section: Discussionmentioning
confidence: 99%
“…22,24,25 There is evidence that allele I of ACE gene is associated with lower ACE levels, whereas D allele is associated with increased ACE activity. 26,27 Few studies demonstrate genderrelated comparisons with genes, regarding multifactorial disorders as stroke, and refer to oestrogen receptor genes. 28,29 Regarding ACE gene, a limited number of studies demonstrate certain differences regarding gender, such as the higher levels of Ang-I and Ang-II in DD females in a series of healthy individuals 22 and the higher levels of renin and prorenin levels in DD women.…”
Section: Discussionmentioning
confidence: 99%